Tissue Doppler and strain imaging of left ventricle in Beagle dogs with iatrogenic hypercortisolism - Oui, Heejin (J Vet Sci, 2015)
Changes in radial and longitudinal left ventricular (LV) function were investigated in beagles with iatrogenic hypercortisolism. A total of 11 normal dogs were used, and 2 mg/kg prednisone was administered per oral q12 h for 28 days to 7 out of 11 dogs to induce iatrogenic hypercortisolism. Body weight, blood pressure, conventional echocardiography and tissue Doppler imaging (TDI) of normal and iatrogenic hypercortisolism groups were conducted. The myocardial wall velocity of the LV was measured using color TDI and myocardial deformation was determined by the strain and strain rate. Conventional echocardiography revealed that the diastolic LV free wall and interventricular septum in the hypercortisolism group were thickened relative to those in the normal group. The peak early diastolic myocardial velocity and early to late diastolic myocardial velocity ratio of TDI in the hypercortisolism group were significantly lower than those in the normal group. The strain values in the hypercortisolism group were significantly lower than those in the normal group, particularly for longitudinal wall motion. The lower values of myocardium from TDI and strain imaging could be used to investigate subclinical LV systolic and diastolic dysfunction in dogs with the iatrogenic hypercortisolism.